Research on the relationship between relational capital and relational rent - Li Zhang; Jiafure Wang (Cogent Economics & Finance, 2018)
Background : With the development of world economic globalization and the advent of the sharing economy era, the competition is not existed between individual enterprises any more, while upgraded to be the competition and cooperation among partners. It is difficult for enterprises to obtain excessive profits only by internal resources and their own management. Therefore, they need to break through the limitation of internal resources and abilities to create new forms of excessive profits with their partners. Purpose : The purpose of this research, under theoretical frameworks of social capital and relational view, is to study the relationship between relational capital, which is an intangible resource, and relational rent as to find more theoretical basis for the cooperative enterprises. Research design, data, and methodology : Based on the analysis of the relevant literature, this re- search comes up with the idea that the formation of relational capital (including the approaches of trust and commitment) is via capital rent (involving Relational- specific Assets, Knowledge sharing Routines ? Complementary Resources ? Effective Governance) and then further puts forward the hypothesis and conceptual model of 'relational capital' affecting 'relational rent'. The current study selected Chinese manufacture industry as a sample frame and collected data from 304 respondents. Data were analyzed using structural equation model to test the hypotheses. Results : Through empirical study, it was found that trust and commitment have significant effects on knowledge sharing, complementary resources and co-governance, and there is no remarkable effect on the relationship-specific investment
Keywords: 330; relational rents; competition; information sharing; supply chain; relational capital